Pengaruh Pemberian Kredit Usaha Rakyat (Kur) Bri Pada Pendapatan Dan Efesiensi Usaha Peternak Ayam Broiler Di Kecamatan Selesai Kabupaten Langkat - Dicky Dicky; Syaifuddin Syaifuddin; Yusniar Lubis (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2023)
The state of small businesses in indonesia's economic position is very important, especially after the economic crisis hit Indonesia in 1998.  The economic crisis has proven that the durability of small businesses is more resilient when compared to most large businesses. Several factors that cause the low effectiveness of these programs, first the support program for small business development is limited to issues or credit programs, these programs also do not actually increase the growth of small businesses.  This research aims to find out and analyze the effect of KUR BRI granting on the income of broiler chicken farmers in The District of Selesai Langkat Regency. To find out and analyze the effect of kur bri grant on the financial efficiency of broiler chicken farms in The District of Selesai Langkat Regency.  The data used is primary data sourced from breeders of 40 petewrnak by providing a list of questionnaires.  The research model is a quantitative model using multiple linear regression analysis techniques that use the SPSS program version 16.0. From the results of the study showed that the provision of KUR BRI had a significant effect on the income and financial efficiency of broiler chicken farmers in The District of Selesai Langkat Regency.